Diabetes Self-management Intervention Based Smartphone Application in Patients With Diabetes Mellitus: Systematic Review - Syafitri, Mea Kuraini; Astri, Nur Arifah; Ilmiatun, Nur Annisa (STRADA : Jurnal Ilmiah Kesehatan, 2021)
Diabetes is a debilitating health condition that’s rapidly increasing in prevalence globally. Patients with diabetes require education about the disease to improve their knowledge, in which smartphone applications help improve diabetes care and self-management. This study aimed to determine the effectiveness of smartphone application-based self-management interventions in diabetes mellitus patients. Five online databases (Science direct, Scopus, ProQuest, Springer Link and SAGE) was employed. Studies published in English from 2015-2021 were considered. Only randomized controlled trials of application-based self-management intervention in patients with diabetes mellitus. Total of 374 articles were found and ten studies were selected in this systematic review. There are many diabetes related mobile apps like Diaguru, Calendar App, Sidekick Health, Bluestar, GlycoLeap that mainly focusing on self-management of diabetes, lifestyle modiﬁcation, and medication adherence motivation. Smartphone application-based diabetes self-management intervention have beneficial effects on self-efficacy, self-care activities, quality of life and clinical outcomes for diabetes mellitus patient